2020
DOI: 10.21203/rs.3.rs-36422/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular and Clinical Characterization of LAG3 in Breast Cancer Through 2994 Samples

Abstract: Background Despite the promising impact of cancer immunotherapy targeting CTLA4 and PD1/PDL1, a large number of cancer patients fail to respond. LAG3 (Lymphocyte Activating 3), also named CD233, is a protein Coding gene served as alternative inhibitory receptors to be targeted in the clinic. The impact of LAG3 on immune cell populations and co-regulation of immune response in breast cancer remained largely unknown. Methods To characterize the role of LAG3 in breast cancer, we investigated transcriptome data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Reports have suggested that LAG3 co-functions with PD-L1 and PD-1 (12,31). In vivo experiments have shown that T cells may be activated if one of the pathways is blocked.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have suggested that LAG3 co-functions with PD-L1 and PD-1 (12,31). In vivo experiments have shown that T cells may be activated if one of the pathways is blocked.…”
Section: Introductionmentioning
confidence: 99%